A Sequential Logic iLab Utilizing NI ELVIS II+ and the Interactive iLab Architecture - Mwikirize, Cosmas (International Journal of Online and Biomedical Engineering (iJOE), 2012)
Recent trends in development and utilization of online laboratories have resulted into standard platforms that are not lab-specific, which can be leveraged to develop laboratories in diverse fields. One such platform is the Massachusetts Institute of Technology (MIT) interactive iLab Shared Architecture. This paper presents work undertaken at Makerere University to develop a synchronous sequential logic iLab based on this architecture. The research was carried out by a Graduate researcher, under joint supervision in the confines of the iLab Africa Graduate Fellowship Programme. The research builds on previous work undertaken by the same researcher, in which a combinational digital logic iLab was developed. The sequential logic iLab utilizes the National Instruments Educational Laboratory Virtual Instrumentation Suite (NI ELVIS II+) hardware, with its interactive user interface developed using the Laboratory Virtual Instrument Engineering Workbench (LabVIEW). The generic platform supports experiments in the fields of counters, shift registers, frequency dividers and digital clocks, with appropriate electronic component selection and configuration. The design methodologies and implementation strategies for each experiment category are presented as well as the respective test runs. The laboratory has been used to support courses in the curricula of the Bachelor of Science (B.Sc) in Computer, Electrical and Telecommunication Engineering Programmes at Makerere University.